2012
DOI: 10.1007/s00464-012-2350-0
|View full text |Cite
|
Sign up to set email alerts
|

The value of multiple rapid swallows during preoperative esophageal manometry before laparoscopic antireflux surgery

Abstract: Background When multiple swallows are rapidly administered, esophageal peristalsis is inhibited, and pronounced lower esophageal sphincter relaxation ensues. After the last swallow of the series, a robust contraction sequence results. The authors hypothesize that multiple rapid swallows (MRS) may have value in predicting esophageal transit symptoms in patients undergoing laparoscopic antireflux surgery (LARS). Methods Records of patients undergoing esophageal high-resolution manometry (HRM) before LARS were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 13 publications
0
81
0
5
Order By: Relevance
“…It is worth noting that all patients had complete inhibition of esophageal body motility during MRS. Similarly, Stoikes et al 18 observed that the inhibition phase during MRS remained intact both in the esophageal body and in the LES in patients with suboptimal DCI and late postoperative dysphagia, suggesting that the contractile defect is not within the inhibitory pathways. Data from this study showed that MRS DCI and MRS/ WS ratio were inversely correlated with AET, but directly correlated with BI values and PSPW index.…”
Section: Discussionmentioning
confidence: 95%
“…It is worth noting that all patients had complete inhibition of esophageal body motility during MRS. Similarly, Stoikes et al 18 observed that the inhibition phase during MRS remained intact both in the esophageal body and in the LES in patients with suboptimal DCI and late postoperative dysphagia, suggesting that the contractile defect is not within the inhibitory pathways. Data from this study showed that MRS DCI and MRS/ WS ratio were inversely correlated with AET, but directly correlated with BI values and PSPW index.…”
Section: Discussionmentioning
confidence: 95%
“…50 Whether the occurrence of postoperative dysphagia can be predicted by oesophageal motility testing performed preoperatively remains a matter of debate. However, some encouraging data suggest that subtle, subclinical dysfunctions of motility, detectable by combined pressureimpedanc e analysis 52,53 and/or multiple rapid swallow testing, 54 could predict susceptibility to postoperative dysphagia. Although these data are preliminary, they suggest the potential for an individual patient's risk for dysphagia to be better quantified than is currently possible.…”
Section: Gerd-related Dysphagiamentioning
confidence: 98%
“…Drinking from the cup is more physiological but not always easier, because if more than three seconds elapse between swallows the test is no longer valid (94). The RS test is especially suitable for patients with hypomotility, as it allows the functional peristaltic reserve that has been linked with the appearance of dysphagia after fundoplication (91,95,96) to be assessed.…”
Section: Current Situationmentioning
confidence: 99%